Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 9 - Roots and Radicals - 9.5 - Solving Radical Equations - Problem Set 9.5 - Page 424: 25



Work Step by Step

Squaring both sides of the equation and then using the properties of equality, we obtain: \begin{array}{l}\require{cancel}\left( \sqrt{x+3} \right)^2=\left( x+3 \right)^2 \\\\ x+3=(x)^2+2(x)(3)+(3)^2 \\\\ x+3=x^2+6x+9 \\\\ 0=x^2+(6x-x)+(9-3) \\\\ x^2+5x+6=0 \\\\ (x+3)(x+2)=0 \\\\ x=\{-3,-2\} .\end{array} Upon checking, both solutions satisfy the original equation. Hence, $ x=\{-3,-2\} .$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.